Measurement of dynamic electrokinetic effects at the glass/electrolyte interface using a mega-Hertz-level mechanical wave - Aremanda, Sudeepthi; Li, Yifan; Onuh, Gideon; Manor, Ofer (Frontiers in Acoustics, 2025)
We measured the dynamic electrical properties of a spontaneously charged glass surface in an electrolyte solution by using a MHz-level surface acoustic wave (SAW) actuator to introduce a same-frequency mechanical wave into the glass substrate. The mechanical wave vibrated ions in the nanometer-thick electrical double layer (EDL) to appear at the glass/electrolyte interface. The out-of-equilibrium EDL leaked an electrical field, which was modulated by ion vibration frequency to reveal the presence of ions and their dynamic motion. A previous study excited EDLs on the piezoelectric lithium niobate substrate of a SAW actuator in contact with an electrolyte solution, but it remained unclear whether the mechanical or electrical components of the SAW in the piezoelectric substrate dominated the EDL excitation. Here, we isolated the SAW mechanical component in glass and showed that it introduces a similar ion electrokinetic vibration in the excited EDL at the glass/electrolyte interface using sodium nitrate and potassium chloride solutions as electrolytes. The measured electrical field leakage spectra were of similar magnitude to those measured in the previous study and exhibited similar non-monotonic behaviors, taking local maxima where the SAW period (the inverse of its frequency) was synchronized with the ion relaxation times in the EDL. At these frequencies, the synchronization maximized ion vibration displacement, thereby amplifying the electrical field leakage. Our findings may be used to study the electrokinetic properties of solid surfaces and ion dynamics in EDLs. Moreover, SAW-actuated fluidic platforms may support out-of-equilibrium EDLs relevant to ion-selective membranes and the film stability of electrolyte solutions.